Decimals. [Student Worksheets for Vocational Agricultural Courses] Larry R. Jewell. - Jewell, Larry R. (Distributed by ERIC Clearinghouse, 1985)
This learning module provides students with practice in applying mathematical operations to vocational agriculture. The module consists of unit objectives, definitions, information, problems to solve, worksheets suitable for various levels of vocational agriculture instruction, and answer keys for the problems and worksheets. This module, which covers decimals, provides practice in activities such as converting fractions to decimals and converting decimals to fractions; and addition, subtraction, multiplication, and division of decimals. These concepts are shown through applications such as determining housing needs for various kinds of farm animals, and estimating cost of materials for a job. (KC)